Pengaruh Kedisiplinan dan Kemandirian Belajar terhadap Kemampuan Pemecahan Masalah Matematika - Yuliana Ayundhaningrum; Roida Siagian (Universitas Indraprasta PGRI, 2017)
The aims of study to determine: (1) The Effect of Decipline and Learning Independence on Math Problem Solving Skills, (2) The Effect of Decipline on Math Problem Solving Skills, (3) The Effect of Learning Independence on Math Problem Solving Sklls. Data collection Technique by giving a questionnaire for independent variables and giving a question (essay) for dependent variable. The samples taken in this study came from an affordable population of Senior High School Tulus Bhakti class X in Bekasi, on school year 2016/2017 with the sampling technique by means of simple random sampling. This research methods used is survey with multiple regression statistic analysis technique. The result concluded, (1) There is a significant influence on Decipline and Learning Independence on Math Problem Solving Skills. (2) There is a significant influence on decipline on Math Problem Solving Skills. (3) There is a significant influence on learning independence on Math Problem Solving Skills.